Kinetics of interaction between beta-receptors, GTP protein, and the catalytic unit of turkey erythrocyte adenylate cyclase. - Tolkovsky, A M (1982)
The kinetics of turkey erythrocyte membrane adenylate cyclase activation by beta-agonists and guanyl-5'-yl imidodiphosphate is explored as a function of the concentration of the GTP regulatory protein and of the catalytic unit. It was found that the overall kinetics of activation is first order and is independent of the concentration of the GTP regulatory unit N, the catalytic unit C, and of hormone over a very wide concentration range. It was established that the rate-limiting step does not involve GDP dissociation from the inactive N unit or the association between activated N' and C. Also, it was found that guanyl-5'-yl imidodiphosphate binding occurs in a random fashion and is not hormone dependent. These results enable us to exclude models of the sequential type in which N in its inactive form is bound to receptor R, is released in an active form N' upon hormone activation, and then binds to C, activating the latter. An acceptable model that accounts for all of the data conforms to the original formulation of "collision coupling" in which N is tightly associated to C at all times.